A simple protein-energy wasting score for survival prediction of maintenance hemodialysis patients. Issue 1 (December 2015) - Kobayashi, Sonomi; Suzuki, Keiko; Ueda, Mio; Tanaka, Yoshiko; Nitta, Kosaku
Abstract Background The nutritional status of patients on maintenance hemodialysis (MHD) is a strong predictor of their survival. We assessed the reliability of a protein-energy wasting (PEW) score as a predictor of the survival of Japanese MHD patients. Methods The study subjects were 254 MHD patients. PEW score was from 0 (worst; group 1) to 4 (best; group 4) and was derived from four body nutrition compartments: serum albumin, body mass index, a normalized serum creatinine value, and protein intake. The main outcome was all-cause mortality. Results A total of 26 patients died during the follow-up period of 36 months. The Kaplan-Meier analysis revealed that the group whose score was 0–1 had a significant lower survival rate than the groups with higher (2–4) PEW scores (P  < 0.0001). In multivariate analysis, hazard ratios (HRs) were 0.214 (confidence interval (CI) 0.068–0.610, P  < 0.005) between group 1 and group 4, 0.176 (0.054–0.510, P  < 0.005) between group 2 and group 4, and 0.249 (CI 0.054–0.857) between group 3 and group 4. Conclusions A new simple PEW score predicts the survival of MHD patients and may help to better identify subgroups of MHD patients with a high mortality rate.